A Risk-Benefit Analysis of Increasing Surgical Invasiveness Relative to Frailty Status in Adult Spinal Deformity Surgery. Issue 16 (15th August 2021) - Passias, Peter G.; Brown, Avery E.; Bortz, Cole; Pierce, Katherine; Alas, Haddy; Ahmad, Waleed; Passfall, Lara; Kummer, Nicholas; Krol, Oscar; Lafage, Renaud; Lafage, Virginie; Burton, Douglas; et al.
Abstract : Study Design: Retrospective review of a prospectively enrolled multicenter Adult Spinal Deformity (ASD) database. Objective: Investigate invasiveness and outcomes of ASD surgery by frailty state. Summary of Background Data: The ASD Invasiveness Index incorporates deformity-specific components to assess correction magnitude. Intersections of invasiveness, surgical outcomes, and frailty state are understudied. Methods: ASD patients with baseline and 3-year (3Y) data were included. Logistic regression analyzed the relationship between increasing invasiveness and major complications or reoperations and meeting minimal clinically important differences (MCID) for health-related quality-of-life measures at 3Y. Decision tree analysis assessed invasiveness risk-benefit cutoff points, above which experiencing complications or reoperations and not reaching MCID were higher. Significance was set to P < 0.05. Results: Overall, 195 of 322 patients were included. Baseline demographics: age 59.9 ± 14.4, 75% female, BMI 27.8 ± 6.2, mean Charlson Comorbidity Index: 1.7 ± 1.7. Surgical information: 61% osteotomy, 52% decompression, 11.0 ± 4.1 levels fused. There were 98 not frail (NF), 65 frail (F), and 30 severely frail (SF) patients. Relationships were found between increasing invasiveness and experiencing a major complication or reoperation for the entire cohort and by frailty group (all P < 0.05). Defining a favorable outcome as no major complications or reoperation and meeting MCID in any health-related quality of life at 3Y established an invasiveness cutoff of 63.9. Patients below this threshold were 1.8[1.38–2.35] ( P < 0.001) times more likely to achieve favorable outcome. For NF patients, the cutoff was 79.3 (2.11[1.39–3.20] ( P < 0.001), 111 for F (2.62 [1.70–4.06] ( P < 0.001), and 53.3 for SF (2.35[0.78–7.13] ( P = 0.13). Conclusion: Increasing invasiveness is associated with increased odds of major complications and reoperations. Risk-benefit cutoffs for successful outcomes were 79.3 for NF, 111 for F, and 53.3 for SF patients. Above these, increasing invasiveness has increasing risk of major complications or reoperations and not meeting MCID at 3Y. Level of Evidence: 3 Abstract : Adult spinal deformity (ASD) is a complex pathology resulting in debilitating pain and disability. To assess magnitude of correction necessary, the ASD Invasiveness Index was developed. However, the impact of certain risk factors and physiological states such as frailty on this index has been understudied in the literature.